Nitrite contents in various masticatories prevailing in the state of Assam – a pilot study - Bharadwaj, Rituraj; Barooah, Prajjalendra; Saikia, Snigdha; Haloi, Jayanta; Deka, Manab; Sahu, Bhanu P; Medhi, Subhas (Journal of Applied Pharmaceutical Research, 2017)
Background: The habit of using masticatories is quite common among the population of the state Assam. There are numerous types of masticatories available throughout the state, most of which include areca nut in different forms, accompanied with beetle leaves and tobacco leaves and other associated substances added for flavor. Aim: To determine the level of nitrite present in different types of masticatories prevailing in the state. Materials & Methods: The classical Griess method was used for the estimation of nitrite in different types of these masticatories prevailing in the state Assam (n=35) using the basic diazotization principle and spectrophotometric determination. Statistical Analysis used: The results obtained were analyzed statistically by using SPSS V.16 software. Results: The result of the study indicate the amount of nitrite in different types of these masticatories, among which highest levels of nitrite was found in raw areca nut with beetle leaves without lime. The presence of lime decreases the amount of nitrite (p<0.05) whereas, the presence of beetle leaves and unprocessed areca nut increases the amount of nitrite (p<0.05) in the masticatories used by the people of the state. Conclusion: From the study conducted, it can be concluded that the presence of lime reduces the amount of nitrite in the masticatories, whereas the presence of beetle leaves and unprocessed areca nut contribute higher amount of nitrite in the masticatories